From Bully Victimization to Aggressive Behavior: Applying the Problem Behavior Theory, Theory of Stress and Coping, and General Strain Theory to Explore Potential Pathways. Issue 21 (November 2021) - Lee, Jeoung Min; Kim, Jinwon; Hong, Jun Sung; Marsack-Topolewski, Christina N.
Studies have documented that some bully victims fall into a subcategory of bullying called "bully victims" in which the victim becomes the aggressor. However, studies to date have not examined the pathways linking bully victimization and aggressive behavior. To address this research gap, this study applies the problem behavior theory, theory of stress and coping, and general strain theory to explore possible pathways from bully victimization to aggressive behavior by examining the mediating effects of low life satisfaction, drug use, and exposure to peer deviance. Structural equation modeling was used to examine the path model from a sample of 1, 676 adolescents, aged 13 to 17 years. Data were derived from the Health Behavior in School-Aged Children (HBSC) survey. Findings revealed that bully victimization was positively associated with aggressive behavior. Moreover, bully victims displayed lower levels of life satisfaction. In addition, bully victims who were frequently exposed to peer deviance and drug use were likely to engage in bullying. These findings support the problem behavior theory and general strain theory and have implications for research, practice, and policy.